Answer:
input = 5
Step-by-step explanation:
y = -2x - 6
When y = -16
-16 = -2x - 6
divide by -2 on both sides,
8 = x + 3
x = 8 - 3 = 5
Let: eq 1:2x+5y=-55
eq 2:y=3x+6
by substituting eq 2 in eq 1 we get,
2x+5(3x+6)=-55
2x+15x+30+55=0
17x + 85=0
x=-85/17
x=-5
By substituting x value in eq 2,
we have,
y=3(-5)+6=-15+6=-9
Answer:
y=-5x+30
Step-by-step explanation:
I HOPE THIS HELPS
BRAINLIEST PLSSS I NEED IT SO BAD
Answer:
![-\frac{6}{7}](https://tex.z-dn.net/?f=-%5Cfrac%7B6%7D%7B7%7D)
Step-by-step explanation:
⇒ ![m = \frac{y_{2} - y_{1}}{x_{2} - x_{1}}](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7By_%7B2%7D%20-%20y_%7B1%7D%7D%7Bx_%7B2%7D%20-%20x_%7B1%7D%7D)
⇒ ![m = \frac{9 - 3}{1 - 8}](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7B9%20-%203%7D%7B1%20-%208%7D)
⇒ ![m = \frac{6}{-7}](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7B6%7D%7B-7%7D)